2012
DOI: 10.1097/rlu.0b013e318239248b
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT in Differentiation of Pseudarthrosis From Other Causes of Back Pain in Lumbar Spinal Fusion

Abstract: In the lumbar spine, SPECT/CT seems to increase specificity for detection of nonunion of interbody devices compared with CT alone. It is more sensitive than CT to detect facet joint degeneration, and it can detect screw loosening as well as CT. These findings can be helpful for surgeons in planning appropriate surgical revision strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
1
27
0
3
Order By: Relevance
“…Damgaard et al [52] performed such a study and indeed showed that this evaluation confirmed the SPECT/CT diagnosis of metal loosening in their sample of nine patients suffering from lower back pain after lumbar instrumentation. Similar data have been published by Rager et al [53]: in their case series of ten patients, all screws deemed loosened on reoperation had corresponding increased tracer uptake on SPECT/CT. In six cases, metabolic activation was found in facet joints that had no CT abnormality, and in three of five subjects SPECT/CT did not confirm the CT diagnosis of nonunion through or around cages.…”
Section: Differential Diagnosis Of Pain Associated With the Musculosksupporting
confidence: 76%
“…Damgaard et al [52] performed such a study and indeed showed that this evaluation confirmed the SPECT/CT diagnosis of metal loosening in their sample of nine patients suffering from lower back pain after lumbar instrumentation. Similar data have been published by Rager et al [53]: in their case series of ten patients, all screws deemed loosened on reoperation had corresponding increased tracer uptake on SPECT/CT. In six cases, metabolic activation was found in facet joints that had no CT abnormality, and in three of five subjects SPECT/CT did not confirm the CT diagnosis of nonunion through or around cages.…”
Section: Differential Diagnosis Of Pain Associated With the Musculosksupporting
confidence: 76%
“…These studies suggest that rigid fixation and fusion increase patient satisfaction. However, it was reported that pseudarthrosis may develop in 5-25% of patients who underwent PLF and 50% of patients with pseudarthrosis may be asymptomatic (23). Moreover, it was reported that short-term results of dynamic systems which have been started to be used in degenerative spondylolisthesis in recent times were successful and similar to the results of fixation and PLF (24,25).…”
Section: Discussionmentioning
confidence: 75%
“…Selon certaines guidelines, la scintigraphie osseuse n'est pas recommandée pour l'évaluation de la fusion osseuse [18], mais ces recommandations se basent sur un seul article déjà ancien et sans acquisition TEMP. Rager et al [19] ont comparé les résultats de scintigraphies osseuses par TEMP/TDM et des scanners de 10 patients. Ils ont montré une bonne sensibilité pour l'évaluation des DMA et des descellements de vis et une bonne spécificité pour la détection des PA inter-somatiques par rapport à la TDM.…”
Section: Discussionunclassified
“…La PA, qui est définie par une nonunion de la greffe 6 mois après l'intervention, est une complication fréquente des arthrodèses [23,24]. Son incidence varie de 5 à 56 % en fonction des séries [19]. Les facteurs de risque pour développer une PA sont l'âge du patient, la présence d'une ostéopénie, le tabagisme actif, la présence d'une infection postopératoire et les traitements par corticoïdes ou AINS [6,19].…”
Section: Les Pseudarthrosesunclassified
See 1 more Smart Citation